2014
DOI: 10.9753/icce.v34.structures.20
|View full text |Cite
|
Sign up to set email alerts
|

Single-Layer Breakwater Armouring: Feedback on the Accropodetm Technology From Site Experience

Abstract: The single-layer technique appeared at the beginning of the 1980s, with the ACCROPODE™ unit, and is thus entering its third decade. At the time, this solution was a real innovation, reducing the amount of concrete and steepening armour facing slopes, hence reducing the volume of materials required. After three decades in use and more than 200 projects to date, it was important to summarize the lessons learned during this period and to inspect (above and below water) some of these structures in order to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Several studies have reported that the environment has a strong impact on the colonization of cementitious materials in the marine context (Giraudel, Garcia, and Ledoux, 2014; Lors, Feugeas, and Tribollet, 2019; Souche et al ., 2019). The medium influences the development and growth of microorganisms as well as the aging of the material.…”
Section: Methods: Physicochemical Factors Influencing the Colonizatio...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that the environment has a strong impact on the colonization of cementitious materials in the marine context (Giraudel, Garcia, and Ledoux, 2014; Lors, Feugeas, and Tribollet, 2019; Souche et al ., 2019). The medium influences the development and growth of microorganisms as well as the aging of the material.…”
Section: Methods: Physicochemical Factors Influencing the Colonizatio...mentioning
confidence: 99%
“…Artificial marine structures modify, positively or negatively, the natural environment (Azevedo et al ., 2006) to become part of a new ecosystem (Giraudel, Garcia, and Ledoux, 2014). Then to avoid high negatives impacts, as frequently seen, the ecological mechanism of settlement on concrete needs to be assessed before their implementation (Baine, 2001; Bulleri and Chapman, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soulignons qu'il s'agit d'une démarche de restauration écologique et non d'une artificialisation des milieux naturels qui viserait la création d'une nouvelle "nature", aux fonctionnalités écologiques non préexistante, ni viable en dehors de toute intervention humaine d'entretien. Il s'agit pour cela de connaitre les processus naturels de colonisation par des organismes vivants marins, sur des types d'habitats naturels comme sur des ouvrages artificiels (GIRAUDEL et al, 2014). Il devient dès lors prioritaire, dans un double objectif de protection de l'environnement et de l'ouvrage, de comprendre également les mécanismes de peuplement qui pourraient altérer ou protéger l'ouvrage mais également le vivant qui le colonise (BAINE, 2001 ;AZEVEDO et al, 2006 ;BULLERI & CHAPMAN, 2010 ;SOUCHE et al, 2016).…”
Section: Introductionunclassified